2008
DOI: 10.1002/qua.21631
|View full text |Cite
|
Sign up to set email alerts
|

Structures and energies of ArnH2O (n = 1–26) clusters using a nonrigid potential surface: A molecular dynamics simulation

Abstract: Stable structures and minima energies of Ar n H 2 O (n ϭ 1-26) clusters are determined by carrying out a stochastic search method coupling to molecular dynamics calculations. A nonrigid intramolecular potential surface together with a pairwise-additive intermolecular potential are used. A growing pattern mechanism is described for the structures in the ground state and a solvation process is observed. Molecular relaxation effects are characterized and the second differences on the cluster binding energies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Such structures were actually found as the global minima in FF calculations, for n = 13 58 or for n = 12,13. 59 With the SCC-DFTB/FF model, they are actually not the global minima for n = 11, 12, or 13 but local minima lying +11, +55, or +91 cm −1 above the global minima, respectively. We now discuss the energetics, and in particular the values of E cohes /n defined as the normalized values of the evaporation energy associated with the reaction H 2 OAr n → H 2 O + nAr (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such structures were actually found as the global minima in FF calculations, for n = 13 58 or for n = 12,13. 59 With the SCC-DFTB/FF model, they are actually not the global minima for n = 11, 12, or 13 but local minima lying +11, +55, or +91 cm −1 above the global minima, respectively. We now discuss the energetics, and in particular the values of E cohes /n defined as the normalized values of the evaporation energy associated with the reaction H 2 OAr n → H 2 O + nAr (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…For larger H 2 OAr n clusters (n = 4−13), we compared the SCC-DFTB/FF structures to those obtained by force-field (FF) calculations available in the literature. 58,59 For all SCC-DFTB/ FF minima for n ≤ 13, the H 2 O molecule is found at the surface of the cluster (Figure 3). For n ≤ 9, our results are consistent with the FF calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Borges et al have further calculated the structures of (H2O)Arn (n = 1 -26), and found that as the cluster size increases, the Ar atoms prefer to stack alongside the oxygen of H2O asymmetrically until the central H2O is completely solvated when n ≥ 12. 49 It is reasonable to deduce that more Ar atoms are required to completely encapsulate the larger (H2O)n clusters, compared with the relatively smaller C2H2 core, and such differentiation in the stacking pattern may account for the origin of discrepancies in Rydberg states between (C2H2)Arn and (H2O)mArn. Also, the compact stacking of the Ar is not predicted in our calculations, especially for n = 4, which exhibits a rhomboid stacking of the Ar atoms instead of a tetrahedron.…”
Section: A Comparison To the Ar-water Systemmentioning
confidence: 99%
“…When the number of argon atoms is sufficiently high, coreshell (water-argon, respectively) type configuration can also take place. 2,8,9 The example structure illustrated in the abstract figure is taken from Lu et al 9 Mass spectroscopic studies of argon-water clusters, mainly upon (inner/outer) valence ionization, have been previously carried out at least by Shinohara et al, 10 Jongma et al, 11 Golan and Ahmed, 12 and Koc ˇis ˇek et al 2 It has been found that ionization of the argon matrix can act as a mediator for water cluster ionization, and also provide cooling for the water cluster cation via neutral evaporation. 2,11,12 Excitonic charge transfer reactions from argon to water were observed with resonant VUV excitation by Golan and Ahmed, 12 while low energy electron irradiation was examined by Koc ˇis ˇek et al 2 In the present experiment, we exploit high energy (3 keV) electron irradiation to induce core ionization from the 2p-core level of an Ar-site, followed by L 2,3 M 2,3 M 2,3 Auger decay to a one-site doubly ionized state Ar 2+ (3p À2 )ÀAr MÀ1 [H 2 O] N .…”
Section: Introductionmentioning
confidence: 99%